Perlindungan Hukum Terhadap Pekerja Dengan Perjanjian Kerja Waktu Tertentu Di Indomaret Cabang Bireuen Berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta kerja - Ade Soraya (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
A Fixed Time Work Agreement is a work agreement between a worker or laborer and an entrepreneur to enter into a working relationship for a certain time or for a certain job. Specific Time Work Agreements are based on a certain period of time or the completion of a specific job in occordance with a work agreement. The article on specific time work agreements is governed by Article 59 of Law No. 11 of 2020 on job creation. The Indomaret Bireuen branch company, which is engaged in franchising, must comply with and implement the provisions contained in Law Number 11 of 2020 concerning Job Creation. This study aims to determine the forms of legal protection for workers with work agreements for a certain time or contract workers at the Indomaret Bireuen branch and to find out the factors that become obstacles to the implementation of legal protection for workers or labor at the Indomaret Bireuen branch. The method used in this research is empirical juridical research, which is an approach that refers to written regulations to observe their implementation through field research. The results of this study state that legal protection for workers with work agreements for a certain time at the Indomaret Bireuen branch can be said to be in accordance with applicable regulations. However, there are still several forms of legal protection that have not been fully implemented, such as those for workers who still have to work beyond their normal working hours. There are several factors that impede the implementation of legal protection for workers/laborers, including a lack of legal awareness on the part of employers or companies and workers, and factors related to work agreements.